Performance of the VITEK® MS system for the identification of filamentous fungi in a microbiological laboratory in Chile. - Lorena Porte; Rodrigo Cruz; Inia Pérez; Carmen Varela; Cristina Díaz; Patricia García; Paulette Legarraga; Francisca Valdivieso; Thomas Weitzel (PLoS ONE)
Filamentous fungi are an emergent cause of severe infections in immunocompromised patients. Timely and accurate identification is crucial to initiate appropriate therapy. Traditional identification methods are time-consuming, labor-intensive, and operator-dependent. Matrix-assisted laser desorption/ionization-time-of-flight (MALDI-TOF) mass spectrometry is a rapid and easy-to-perform identification method. The effectiveness of a commercial MALDI-TOF MS platform to identify filamentous fungi in a clinical laboratory was evaluated. The study included 67 fungal isolates from 35 species/species complexes, which were identified and confirmed in mycology reference laboratories; 32 derived from clinical samples, 34 from strain collections and one was an ATCC strain. The study used the VITEK® MS system (v3.2.0 database), after sample extraction by VITEK® MS Mould Kit. Results were classified as "correct species", "correct species complex", "correct genus"and "no identification". VITEK® MS correctly identified 91.0% of isolates (58.2% to species, 29.9% to species complex, and 1.5% to genus level only). In 82%, the result matched the species/species complex identified by reference methods. No misidentifications were observed. The kit was rapid and easy to use. In conclusion, the VITEK® MS system showed a high capability to accurately identify filamentous fungi in a clinical laboratory.